Validation of the German version of the Schedule of Attitudes Toward Hastened Death (SAHD-D) with patients in palliative care - Galushko, Maren; Strupp, Julia; Walisko-Waniek, Johanna; Hahn, Moritz; Löffert, Sabine; Ernstmann, Nicole; Pfaff, Holger; Radbruch, Lukas; Nauck, Friedemann; Ostgathe, Christoph; Voltz, Raymond (Palliative & supportive care., 2015)
Reliable and validated instruments are needed in order to study the desire for hastened death (DHD). As there is no instrument in the German language to measure DHD, our aim was to validate a German version of the Schedule of Attitudes Toward Hastened Death (SAHD-D).The SAHD was translated following guidelines promulgated by the European Organization for Research and Treatment of Cancer (EORTC). In eligible patients (clinical situation adequate, MMSE >=21), the following instruments were employed: a symptom checklist (HOPE), the HADS-D (Hospital Anxiety and Depression Scale), the EORTC-QLQ-PAL15, and the SAHD-D, as well as an external estimation of DHD provided by the attending physician. A high level of DHD was defined as the mean plus one standard deviation (SD).Of the 869 patients assessed, 92 were eligible for inclusion (66% females, mean age of 64.5 years). The SAHD-D total score ranged from 0 to 18, with a mean of 5 and a standard deviation (SD) of 3.7. A high level of DHD was found in 20% (n = 19). For discriminant validity, significant correlations were found between the SAHD-D and depression (r rho = 0.472), anxiety (r rho = 0.224), and clinical state (r rho = 0.178). For criterion validity, the external estimate of DHD showed a low significant correlation with patient score (r rho = 0.290). Factor analysis of the SAHD-D identified two factors.Validation of the SAHD-D illustrated good discriminant validity, confirming that a desire to hasten death is a construct separate from depression, anxiety, or physical state. The unidimensionality of the SAHD could not be reproduced. Our findings support the multifactorial interdependencies on DHD and suggest that the SAHD-D should be refined by considering actual wishes, general attitudes, and options of patients.
EVALuna2:26194
Keywords: Desire for hastened death; Palliative care; SAHD; Validation